Activation of Coconut Shell Charcoal and Application for Bleaching Used Cooking Oil - Siti Jamilatun; Martomo Setyawan; Lutfiatul Janah; Rifka Alfiyani; Ilham Mufandi (CHEMICA: Jurnal Teknik Kimia, 2021)
This study aimed to determine coconut shell-activated charcoal's ability in the bleaching process of used cooking oil. Activation of coconut shell charcoal was carried out using 5N H2SO4 solution. Activated charcoal is made through a pyrolysis process at a temperature of 350 â°C for 1 hour. The experiment was carried out in four stages: activation of activated charcoal, testing the characteristics of activated charcoal, bleaching used cooking oil, and testing the characteristics of used cooking oil. The characteristic test of activated charcoal is moisture content, ash content, and iodine absorption rate. Meanwhile, used cooking oil characteristics were carried out in water content, specific gravity, and color test. The results showed that the ash content of activated charcoal was 2.4-2.8 %, the water content of activated charcoal was 0.5-1%, the iodine absorption content was relatively high, namely 371,896-548,745 mg/g. The water content of used cooking oil was 0.493-0.503 %, the specific gravity of used cooking oil was between 0.888-0.892 %, and the absorbance was between 0.001-0.006. The results of this study were standardized using the Indonesian National Standard Method (SNI). The results show that 40 mesh of activated charcoal is better than 20 mesh.